ANTIBACTERIAL ACTIVITY OF A TRYPSIN-CHYMOTRYPSIN-ELASTASE INHIBITOR ISOLATED FROM LAVATERA CASHMERIANA CAMB.SEEDS - S. Rakashanda; M. Ishaq; A. Masood; S. Amin (Journal of Animal and Plant Sciences, 2012)
Protease inhibitors were extracted from the seeds of Lavatera cashmeriana Cambby ammonium sulphate precipitation and purified by chromatography on DEAE-cellulose and Sephadex G-100 column. The bound protein eluted into four major peaks which we named as LC-pi I, II, III and IV, all showing strong anti protease activity against trypsin, chymotrypsin and elastase. LC-pi I was screened for antibacterial activity against Klebsiella pnuemoniae,  Escherichia coli and Pseudomonas aeruginosa. The protease inhibitor showed strong antibacterial activity against Klebsiella pnuemoniae  and Pseudomonas aeruginosa but was less active against  Escherichia  coli.
Keywords: Lavatera cashmeriana Camb; antibacterial activity; LC-pi I; nutrient agar.